Analysis of Financial Performance of Sharia Banking Using the Islamicity Performance Index Approach in Sharia Banking in Indonesia - khatimah, husnul; Akter Rani, Suzanna (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
The Islamic banking sector is pivotal in fostering an economy aligned with Islamic principles, yet conventional performance metrics often fail to capture Sharia compliance comprehensively. This study employs the Islamicity Performance Index (IPI) to evaluate the financial performance of Islamic banks in Indonesia, integrating financial and ethical dimensions. The research addresses the question: How does the financial performance of Islamic banking in Indonesia align with the IPI? Using a qualitative descriptive approach, the study analyses three purposively sampled banks—Bank Muamalat Indonesia, Bank BCA Syariah, and Bank Syariah Indonesia—over the period 2021–2023. The IPI framework assesses five key indicators: Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Directors-Employee Welfare Ratio, and Islamic Investment vs. Non-Islamic Investment. Findings reveal that these banks demonstrate a commitment to aligning operations with Islamic principles, particularly in maintaining 100% Sharia-compliant investments. However, challenges persist, including low zakat contributions, significant welfare disparities between directors and employees, and limited adoption of profit-sharing financing models. These findings underscore the need for Islamic banks to enhance strategic initiatives that prioritize equitable economic development and substantive Sharia compliance, beyond mere formal adherence. Recommendations include strengthening profit-sharing mechanisms and improving zakat and welfare distribution to align with the broader objectives of Islamic economics.